Prof. Halushchak M.O. celebrate 80 anniversary - PCSS, Editorial_Team (Physics and Chemistry of Solid State, 2024)
Halushchak Maryan Oleksiyovych, Head of the Department of General and Applied Physics of the Ivano-Frankivsk National Technical University of Oil and Gas, Honored Education Worker of Ukraine, Academician of the Academy of Sciences of the Higher School of Ukraine, Soros' Professor, Doctor of Physical and Mathematical Sciences, Professor, member of the editorial board of the scientific journal "Physics and Solid State Chemistry "